2020
DOI: 10.1186/s13584-020-00422-0
|View full text |Cite
|
Sign up to set email alerts
|

A rapid assessment of migrant careworkers’ psychosocial status during Israel’s COVID-19 lockdown

Abstract: Background Israel hosts nearly 70,000 migrant careworkers. Migrant careworkers work and live with populations extremely vulnerable to the novel Coronavirus, including the elderly and people with pre-existing physical conditions. This rapid assessment aimed to explore psychosocial status and mental wellbeing of migrant careworkers in Israel during the ongoing Covid-19 pandemic and determine risk and protective factors associated with mental distress, anxiety, and depression. Methods This quantitative study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…Two studies were conducted in each of these countries: Singapore [ 43 , 44 ], Hong Kong [ 45 , 46 ], Italy [ 47 , 48 ], The United States of America [ 49 , 50 ], Spain [ 51 , 52 ] and United Kingdom [ 53 , 54 ]. The remaining studies were conducted in Israel [ 55 ], India [ 56 ], South Korea [ 57 ], Malaysia [ 58 ], Thailand [ 59 ], Japan [ 60 ], Norway [ 61 ], Ethiopia [ 62 ], Chile [ 63 ] and China [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies were conducted in each of these countries: Singapore [ 43 , 44 ], Hong Kong [ 45 , 46 ], Italy [ 47 , 48 ], The United States of America [ 49 , 50 ], Spain [ 51 , 52 ] and United Kingdom [ 53 , 54 ]. The remaining studies were conducted in Israel [ 55 ], India [ 56 ], South Korea [ 57 ], Malaysia [ 58 ], Thailand [ 59 ], Japan [ 60 ], Norway [ 61 ], Ethiopia [ 62 ], Chile [ 63 ] and China [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…The articles’ scores range from seven to nine stars. Of the 18 studies, 17 could be regarded as good quality [ 38 , 39 , 41 43 , 46 , 48 , 54 , 55 57 , 59 64 ] and only one was scored to be of poor quality [ 58 ]. The summary of study quality for longitudinal studies assessed using the NOS scale was presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon might be attributed to the accumulating healthcare burden in this demographic group throughout the pandemic, particularly during the lockdown period, where the impact has been demonstrably prominent. For example, studies focusing on migrants reported an increase in mental health disorders in this demographic [ 40 , 41 ]. Sanitary measures associated with the lockdown have brought the lives of many migrants to a standstill as they faced increased precariousness, financial constraints, and stigmatization by the non-migrant community.…”
Section: Discussionmentioning
confidence: 99%
“…They faced poorer access to health care; job and wage loss, accommodation insecurity, difficulties in finding basic food and hygiene needs and anxiety about family members living in different countries (Adhikari et al 2020 ; Kluge et al 2020 ). Migrant health care professionals had a high level of mental distress and poor general health associated with limited access to personal protective equipment (Attal et al 2020 ).…”
Section: Occupational Health Outcomes For Migrant Workersmentioning
confidence: 99%